The Application Of Cooperative Learning Models To Children At Gmim Kindergarten Hosiana Tumatangtang - Suwaryaningrat, N D E (Universitas Negeri Manado, 2019)
This research aimed to make the learning design possible for the development of motor cycle and the coordination of the eyes, hands, brain of the child and carry out the whole plan with the best. Through cooperative learning methods can improve the fine motor skills of children from an average result of fine motor skills of children in collaborative activities in groups. into a medium used in a game with the aim that children can train their fine motor skills. Through this game children are invited to be able to develop creativity through collaborative activities and can develop fine motor skills through these learning activities. This study uses the Classroom Action Research (CAR) approach according to the Kemmis model and MC Taggart. According to Kemmis and Mc Taggart (in Yunus, 2009: 105) describe action research as a set that aims to improve and evaluate decisions and actions aimed at implementing these actions. The discussion of the results of the study was directed at the implementation of the research cycle I and cycle II by following the 4 stages of research, namely planning, action, observation and reflection. Thus the learning achievement of children is 82% of the target of 80% who are successful, so this study in class II action research was declared successful and no longer needed to be continued in the next cycle. Finally, It can be conclude that Cooperative learning can add insight to the teacher in choosing the right learning model to be applied in class according to the objectives of each learning that will be carried out.Keywords: Application; Cooperative Learning Models; Children; Â Kindergarten